TINDAK TUTUR ASERTIF DALAM INTERAKSI JUAL-BELI DI PASAR BETENG TRADE CENTER (BTC) LANTAI 2 DAN RELEVANSINYA SEBAGAI MATERI AJAR BAHASA INDONESIA DI SEKOLAH MENENGAH ATAS - Khoiri, Elvira Chustiana; Setiawan, Budhi; Rohmadi, Muhammad (Universitas Sebelas Maret, 2020)
This study aims to describe (1) assertive speech acts stating what is used in buying and selling interactions between sellers and buyers in the second floor BTC market in the city of Surakarta; (2) the assertive form of assertive speech act stating that is used in buying and selling interactions between sellers and buyers in the second floor BTC market in the city of Surakarta; (3) the implicature function that appears in assertive speech acts states in the interaction of buying and selling between sellers and buyers in the second floor BTC market in the city of Surakarta; and (4) the relevance of assertive speech acts states in the interaction of buying and selling between sellers and buyers in the 2nd floor BTC market as teaching material for negotiating texts in high schools. This study used a qualitative method using a pragmatic study approach related to speech acts. The results of the study are as follows. First, there are 35 variations of speech data that occur in the interaction of buying and selling between sellers and buyers in the second floor BTC market in the city of Surakarta. Second, from 35 assertive utterances stated in the interaction of buying and selling carried out by the seller and buyer are categorized into two forms of implicature, namely conventional and non-conventional. Third, from 35 speech data analyzed the implicature function that emerged from each speech data in the interaction of buying and selling between sellers and buyers in the second floor BTC market in Surakarta. Fourth, Assertive speech acts state that the buying and selling interactions that arise in the BTC market on the 2nd floor can be considered as negotiating text teaching material on basic competence 3.11 constructing negotiating texts for class X SMA by considering variations and learning objectives to be achieved.